Advances in the Diagnosis and Treatment of Krabbe Disease - David A Wenger; Paola Luzi; Mohammad A. Rafi (MDPI AG, 2021)
Krabbe disease is an autosomal recessive leukodystrophy caused by pathogenic variants in the galactocerebrosidase (GALC) gene. GALC activity is needed for the lysosomal hydrolysis of galactosylceramide, an important component of myelin. While most patients are infants, older patients are also diagnosed. Starting in 1970, a diagnosis could be made by measuring GALC activity in leukocytes and cultured cells. After the purification of GALC in 1993, the cDNA and genes were cloned. Over 260 disease-causing variants as well as activity lowering benign variants have been identified. While some pathogenic variants can be considered "severe," others can be considered "mild." The combination of alleles determines the type of Krabbe disease a person will have. To identify patients earlier, newborn screening (NBS) has been implemented in several states. Low GALC activity in this screening test may indicate a diagnosis of Krabbe disease. Second tier testing as well as neuro-diagnostic studies may be required to identify those individuals needing immediate treatment. Treatment of pre-symptomatic or mildly symptomatic patients at this time is limited to hematopoietic stem cell transplantation. Treatment studies using the mouse and dog models have shown that combining bone marrow transplantation with intra-venous gene therapy provides the best outcomes in terms of survival, behavior, and preservation of normal myelination in the central and peripheral nervous systems. With earlier diagnosis of patients through newborn screening and advances in treatment, it is hoped that more patients will have a much better quality of life.